Spectrum of ovarian tumours- a five year study (Journal of Pathology of Nepal, 2017)
Background: Ovarian tumor is the seventh most common cause of cancer related deaths in female. The aim of this study is to find the, morphological and clinicopathological correlation, gross, histological pattern, and incidence of age distribution of ovarian tumors.Materials and Methods: This retrospective and prospective study was carried out from January 2011 to December 2015. The diagnosis was confirmed by histopathological examination using hematoxylin and eosin stain. Special stains and immunohistochemistry were carried out whenever needed.Results: Out of total 158 cases, 62.65% were benign, 3.79% were borderline, and 33.55% were malignant. Histologically, surface epithelial tumors were the most common (74.06%) followed by germ cell tumours(15.82%) and sex cord–stromal tumors (10.12%).Benign tumors were mostly seen in age group of 20–40 years, borderline 21–40 years, and malignant 50–80 years.Conclusion: Tumors originating from surface epithelium are the most common and their malignant counterparts are more frequent in the elderly age group.